Attitudes of Primary Care Physicians Toward Sickle Cell Disease Care, Guidelines, and Comanaging Hydroxyurea With a Specialist - Joseph Lunyera; Charles Jonassaint; Jude Jonassaint; Nirmish Shah (SAGE Publishing, 2017)
Background: Sickle cell disease (SCD) is a complex chronic disease requiring multidisciplinary care that involves primary care physicians (PCPs) working with a hematologist or SCD specialists. However, PCPs often lack access to SCD specialists and are unaware of SCD guidelines or efficacious treatment. Methods: We partnered with Community Care of North Carolina (CCNC) to identify assigned PCPs for SCD patients with Medicaid across North Carolina. CCNC network administrators distributed a web-based questionnaire for completion. The questionnaire involved 12 self-reported items on a yes-no or a 1 to 5 Likert-type scale that assessed PCP attitudes toward SCD care, awareness of recent guidelines, and comanaging hydroxyurea. Results: Of the 53 PCPs who completed the electronic survey, 73% felt they were comfortable with the number of SCD patients in their practice. Most PCPs reported having infrequent communications with an SCD specialist (67%) and most were also not aware of the 2014 SCD guidelines (66%). Many reported that they would frequently use the new SCD guidelines if provided to them (76%). Furthermore, 51% of PCPs expressed comfort with using mobile apps to access SCD guidelines and provided email contact to receive further information. The majority also reported being comfortable comanaging hydroxyurea with an SCD specialist (65%). Conclusion: Few PCPs in North Carolina were aware of the new SCD guidelines or had regular communication with an SCD specialist. The majority of PCPs, however, demonstrated a favorable attitude toward receiving the SCD guidelines and comanaging hydroxyurea with a specialist. In response to this gap in care, we have developed a mobile-based SCD toolbox specifically for PCPs to provide guidelines, algorithms, and a method to communicate with local SCD specialists. With the interest in receiving these guidelines, we are confident the toolbox will provide an easy to use platform to assist PCPs to utilize the SCD guidelines.